A hollow multi-shell structure composite gradient hydrogel and its preparation method and application
The hollow multi-shell structure composite gradient hydrogel addresses hydrogel patch inefficiencies by using temperature-sensitive PNIPAAM for directional drug penetration and sustained release, enhancing transdermal drug absorption.
Patent Information
- Application Number
- CN202411404770.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Hydrogel transdermal patches suffer from poor mechanical properties, high water content, and difficulty in drug penetration through the stratum corneum, leading to reduced drug absorption and treatment efficiency.
A hollow multi-shell structure composite gradient hydrogel is developed, utilizing temperature-sensitive poly-N-isopropylacrylamide (PNIPAAM) to load micro-nano particles, which respond to skin temperature for directional drug penetration and sustained release.
The hydrogel achieves long-term sustained drug release and enhanced absorption by utilizing the gradient pore structure and temperature-responsive properties, improving transdermal drug delivery efficiency.
Smart Images

Figure CN118903064B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a hollow multi-shell structure composite gradient hydrogel and a preparation method and application thereof. Background Art
[0002] Transdermal drug delivery refers to the gradual release of drugs into the blood circulation through the skin to achieve the purpose of treatment. Due to the existence of the first-pass effect of drugs, after entering the body through oral or other non-intravenous routes, the drugs first undergo metabolism in the liver, resulting in a phenomenon in which the drugs are partially metabolized in the liver before entering the systemic circulation. This may lead to reduced bioavailability of the drug. Transdermal drug delivery can effectively avoid the first-pass effect of drugs caused by oral administration. At the same time, compared with invasive drug delivery methods such as intravenous injection, transdermal drug delivery does not require the use of needles or oral administration, avoiding the discomfort and complications that may be caused by surgical operations or digestive tract problems. It can be interrupted and continued at any time, and is more suitable for the treatment of infants and the elderly. In addition, transdermal drug delivery only requires regular replacement of patches or application of drugs, which is easier to adhere to than frequent oral or injection. At the same time, the size of the patch can be adjusted to meet the specific needs of patients, and it has the characteristics of high patient compliance and individualized adjustment. The various advantages of the transdermal drug delivery system give it great potential in the field of disease treatment.
[0003] Hydrogel material is a hydrophilic polymer material with a three-dimensional network structure formed by cross-linking of multiple chemical bonds such as hydrogen bonds and covalent bonds. Hydrogel can be applied to the skin surface as a transdermal patch to achieve transdermal delivery of drugs. However, due to the high water content of hydrogel, its mechanical properties are poor, and its interior is mostly micron-level macroporous structure, which is not conducive to the long-term sustained release of drugs. In addition, after the drug is released from the hydrogel, it is difficult to penetrate the stratum corneum barrier, thereby reducing the absorption rate of the drug. As a patch, the non-directional penetration of molecules in the hydrogel causes the loss of drugs, reduces the treatment efficiency, and brings many difficulties to the widespread application of hydrogel transdermal patches. The use of micro-nanostructured materials and hydrogel composites can combine the controllable drug release performance of the micro-nanostructure with the environmental responsiveness of the hydrogel to further improve the absorption rate of the drug. Summary of the invention
[0004] The purpose of the present invention is to develop a drug-loaded hollow multi-shell structure composite gradient hydrogel in view of the deficiencies of the prior art, and utilize the temperature-responsive shrinkage characteristics of the temperature-sensitive hydrogel poly-N-isopropylacrylamide (PNIPAAM) to load the hollow multi-shell micro-nano particles into the microporous skeleton of the temperature-sensitive hydrogel, and utilize the density difference of different substances to construct the poly-N-isopropylacrylamide composite gradient hydrogel. The hollow multi-shell structure poly-N-isopropylacrylamide composite gradient hydrogel patch can shrink in response to skin temperature, driving the directional penetration of the hollow multi-shell structure micro-nano particles into the stratum corneum; the multi-level structure of the hollow multi-shell structure helps to achieve the long-term sustained release of drugs in the stratum corneum, thereby improving the absorption of drugs.
[0005] In order to solve the above technical problems, the present invention is implemented through the following technical solutions:
[0006] On the one hand, the present invention provides a hollow multi-shell structure composite gradient hydrogel, which comprises a hollow multi-shell structure and a poly (N-isopropylacrylamide) hydrogel with a gradient degree of cross-linking, wherein the hollow multi-shell structure (Hollow multi-shelled structure, HoMS) is compounded in the pores of the poly (N-isopropylacrylamide) hydrogel through physical or chemical action; the poly (N-isopropylacrylamide) hydrogel is temperature sensitive; the hollow multi-shell structure composite gradient hydrogel has pores with a gradient change from top to bottom, and can release drugs in response to changes in skin temperature.
[0007] Based on the above hollow multi-shell structure composite gradient hydrogel, its preparation method comprises the following steps:
[0008] (1) Preparation of temperature-sensitive hydrogel: N-isopropylacrylamide was added to deionized water, mixed and completely dissolved at room temperature, and then ammonium persulfate and 4-hydroxybutyl acrylate were added and completely dissolved, followed by hydrothermal reaction. After cooling and dialysis, poly N-isopropylacrylamide hydrogel was obtained;
[0009] (2) Preparation of hollow multi-shell structure drug complexes: placing the hollow multi-shell structure microspheres in a vacuum environment, slowly adding the drug solution thereto, performing vacuum loading, and washing to obtain the drug-loaded hollow multi-shell structure;
[0010] (3) Preparation of hollow multi-shell structure composite gradient hydrogel: The poly (N-isopropyl acrylamide) hydrogel is placed in a high temperature environment to shrink it and discharge excess water. Subsequently, a suspension containing a hollow multi-shell structure and a permeation enhancer are dripped onto the poly (N-isopropyl acrylamide) hydrogel at room temperature to allow the suspension to penetrate into the pores of the poly (N-isopropyl acrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropyl acrylamide) hydrogel.
[0011] (4) Preparation of hollow multi-shell structure composite gradient hydrogel patch: The hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel obtained in step (3) is prepared into a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel patch, which comprises, from the inside to the outside, a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel layer, a water absorption layer, and a backing transdermal surface layer.
[0012] In the above steps, the concentration of the N-isopropylacrylamide solution in step (1) is 50-150 mg / mL, more preferably 80-120 mg / mL.
[0013] In the step (1), the concentrations of ammonium persulfate and 4-hydroxybutyl acrylate are 0.5-3 mg / mL and 5-20 mg / mL, respectively, preferably 1 mg / mL and 10 mg / mL, respectively.
[0014] In the step (1), the reaction temperature of the hydrothermal reaction is 150-250°C, preferably 170-220°C.
[0015] In the step (1), the hydrothermal reaction time is 200-300 min, preferably 210-260 min.
[0016] In the step (1), the dialysis time is 12-48 hours, more preferably 24-36 hours.
[0017] In the step (1), the pore size of the obtained poly (N-isopropylacrylamide) hydrogel is 30-250 µm, and the pore size is gradually reduced from top to bottom.
[0018] In the step (2), the hollow multi-shell structure microspheres refer to microspheres having a hollow multi-shell structure, which is not particularly limited in the present invention. There are many methods in the prior art for synthesizing hollow multi-shell structure microspheres.
[0019] In the step (2), the hollow multi-shell structure is one or a mixture of oxides TiO2, SiO2, and Fe2O3.
[0020] In the step (2), the size of the prepared hollow multi-shell structure is 0.5-1.5 µm.
[0021] In the step (2), the drug includes one or two of propranolol hydrochloride, nitroglycerin, clonidine and the like, preferably propranolol hydrochloride.
[0022] In the step (2), the concentration of the drug solution is 20-80 mg / mL, preferably 50 mg / mL.
[0023] In step (2), the solvent used for the drug solution includes one or two of deionized water, methanol, ethanol, and chloroform, preferably methanol.
[0024] In the step (2), the solvent used to clean the residual drug on the surface of the hollow multi-shell layer includes one or two of deionized water, methanol, ethanol, and chloroform, preferably ethanol.
[0025] In the step (2), the number of vacuum loading of the drug is 3-8 times, preferably 5 times.
[0026] In the step (2), the drying time is 12-24 hours, more preferably 18-24 hours.
[0027] In the step (3), the heating temperature of the poly (N-isopropylacrylamide) hydrogel is 40-90°C, preferably 70-80°C.
[0028] In the step (3), the mass ratio of the hollow multi-shell structure to the poly (N-isopropylacrylamide) hydrogel is 1:100-4:100, preferably 4:100.
[0029] In the step (3), the penetration enhancer is one of a water-soluble azone solution, dimethyl sulfoxide, menthol, and sodium dodecyl sulfate, and is more preferably a water-soluble azone solution.
[0030] In step (3), the concentration of the penetration enhancer is 10-80 mg / mL, preferably 20-40 mg / mL.
[0031] In the step (4), the transdermal backing surface layer is an adhesive polymer layer, and the polymer layer is polyacrylic acid, chitosan, pectin, hydroxypropyl cellulose, hydroxypropyl methylcellulose, hydroxyethyl cellulose, or other skin adhesive polymers, preferably polyacrylic acid.
[0032] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0033] In a second aspect, the present invention provides an application of a hollow multi-shell structured composite gradient hydrogel in transdermal drugs.
[0034] The transdermal administration effect of the hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel patch of the present invention on propranolol hydrochloride was verified by the following experiments:
[0035] (1) Establish an in vitro drug transdermal release model using Franz diffusion cell;
[0036] (2) Establish an in vivo animal model to measure the blood drug concentration of mice after administration and the penetration imaging of the hollow multi-shell structure in the skin.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. The present invention prepares a hollow multi-shell structure composite gradient hydrogel material by a simple adsorption method using a hollow multi-shell micro-nano material and a poly (N-isopropylacrylamide) hydrogel. The preparation method is simple and convenient, and can realize the composite of the poly (N-isopropylacrylamide) hydrogel and the multi-shell micro-nano structure under mild conditions, avoiding the influence of high temperature on the drug during the hydrothermal synthesis process of the in situ gelation method, and has high stability and wide applicability.
[0039] 2. The hollow multi-shell structure composite gradient hydrogel material prepared by the present invention can give the composite material excellent mechanical properties by adjusting the proportion of the hollow multi-shell structure, so that the hollow multi-shell structure composite gradient hydrogel can be used as a transdermal patch.
[0040] 3 The hollow multi-shell structure composite gradient hydrogel material prepared by the present invention can achieve directional penetration of the hollow multi-shell structure and drugs into the stratum corneum due to the gradient distribution of the pore structure of the poly (N-isopropylacrylamide) hydrogel, thereby improving the transdermal efficiency.
[0041] 4. The hollow multi-shell structure composite gradient hydrogel transdermal patch prepared by the present invention realizes the sequential release of penetration enhancers and drugs, enhances the penetration of the hollow multi-shell structure and drugs in the stratum corneum, and realizes long-term sustained release of drug molecules through the multi-shell structure, thereby improving the transdermal absorption rate of drugs. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a transmission electron microscope photo of the three-shell TiO2 hollow multi-shell structure material prepared in Example 1 of the present invention;
[0043] Figure 2 This is a scanning electron micrograph of a cross section of the poly (N-isopropylacrylamide) hydrogel prepared in Example 1 of the present invention;
[0044] Figure 3 This is a scanning electron micrograph of the hollow multi-shell structure composite gradient hydrogel obtained in Example 1 of the present invention;
[0045] Figure 4 The mechanical properties diagram of the hollow multi-shell structure composite gradient hydrogel obtained in Examples 1, 6, 7, and 8 of the present invention;
[0046] Figure 5 The swelling and deswelling kinetics of the hollow multi-shell structure composite gradient hydrogel prepared in Example 1 of the present invention;
[0047] Figure 6 This is a comparison diagram of the in vitro transdermal performance of the hollow multi-shell structure composite gradient hydrogel prepared in Example 1 of the present invention;
[0048] Figure 7 This is a diagram showing the sustained release effect of the hollow multi-shell structure composite gradient hydrogel with different shell layers prepared in Example 1 of the present invention;
[0049] Figure 8 This is an H&E staining image of the hollow multi-shell structure composite gradient hydrogel in the skin after percutaneous use;
[0050] Fig. 9 This is a fluorescence image of the hollow multi-shell structure in the skin after the hollow multi-shell structure composite gradient hydrogel of the present invention is used transdermally;
[0051] Fig.10 This is a comparative effect diagram of the in vivo blood drug concentration of the hollow multi-shell structure composite gradient hydrogel prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0053] Example 1, a hollow multi-shell structure TiO2 composite gradient temperature-sensitive poly (N-isopropylacrylamide) hydrogel loaded with propranolol hydrochloride, comprising the following steps:
[0054] (1) Preparation of hollow multi-shell TiO2: A 1.5M sucrose aqueous solution was hydrothermally reacted at 200℃ for 146min, naturally cooled and filtered, washed with water three times, and placed in a 60℃ oven for 16h to obtain a carbon sphere template with a diameter of 2.8μm; the obtained carbon sphere template was dispersed in 30mL of 3M TiCl4 solution, ultrasonicated to make the carbon spheres evenly dispersed, placed in a 30℃ water bath for heating and adsorption for 18h, centrifuged and washed with deionized water three times, placed in a 60℃ oven for drying for 18h, and the precursor was placed in a muffle furnace, heated to 500℃ at 2℃ / min, and kept warm for 3h, and then naturally cooled to obtain three-shell TiO2 hollow spheres. The prepared TiO2 hollow multi-shell structure was characterized by scanning electron microscopy, and it was found that the material was spherical with a size of about 0.5μm ( Figure 1 ).
[0055] (2) Preparation of gradient thermosensitive poly (N-isopropylacrylamide) hydrogel: Add 30 mg of ammonium persulfate (concentration: 1 mg / mL) and 300 μL of 4-hydroxybutyl acrylate (concentration: 10 mg / mL) to 30 mL of deionized water, and place in a reactor at 180 °C for hydrothermal reaction for 240 min. After taking out from the reactor lining, dialyze in 1 L of ultrapure water for 36 h. The obtained poly (N-isopropylacrylamide) hydrogel sample was characterized by scanning electron microscopy, and it was found that the pore size of the poly (N-isopropylacrylamide) hydrogel was between 30 and 200 μm, and the pore size gradually decreased from top to bottom, showing a gradient distribution. ( Figure 2 ).
[0056] (3) Preparation of hollow multi-shell structure drug complex: The hollow multi-shell structure microspheres were placed in a vacuum environment, and 50 mg / mL propranolol hydrochloride methanol solution was slowly added thereto. The drug remaining on the surface was then washed with ethanol several times. The above process was repeated 5 times to obtain a hollow multi-shell TiO2 loaded with drugs ( Figure 3 ).
[0057] (4) Preparation of hollow multi-shell structure composite gradient hydrogel: 1 g of poly (N-isopropylacrylamide) hydrogel was heated at 75 °C and excess water was squeezed out. An aqueous solution containing 10 mg of drug-loaded hollow multi-shell TiO2 (the mass ratio of the drug-containing hollow multi-shell structure to poly (N-isopropylacrylamide) hydrogel was 1:100) and 30 mg / mL of azone was added to the poly (N-isopropylacrylamide) hydrogel to allow the hollow multi-shell structure to completely penetrate into the poly (N-isopropylacrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel.
[0058] (5) Preparation of hollow multi-shell structure composite gradient hydrogel patch: The hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel is prepared into a hollow multi-shell structure composite gradient hydrogel patch, which includes, from the inside to the outside, a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel layer, a water absorption layer, and a polyacrylic acid backing transdermal surface layer containing a medical adhesive. Example 2
[0059] A hollow multi-shell structure TiO2 composite gradient temperature-sensitive poly-N-isopropylacrylamide hydrogel loaded with clonidine comprises the following steps:
[0060] (1) Preparation of hollow multi-shell TiO2: A 1.5 M sucrose aqueous solution was hydrothermally reacted at 200 °C for 146 min, naturally cooled and filtered, washed with water three times, and placed in a 60 °C oven for 16 h to obtain a carbon sphere template with a diameter of 2.8 μm; the obtained carbon sphere template was dispersed in 30 mL of 3 M TiCl4 solution, and the carbon spheres were evenly dispersed by ultrasound. The product was placed in a 30 °C water bath for heating and adsorption for 18 h, centrifuged and washed with deionized water three times, and dried in a 60 °C oven for 12 h to obtain a precursor. The product was placed in a muffle furnace, heated to 500 °C at 2 °C / min, and kept warm for 3 h. After natural cooling, it was obtained to obtain a three-shell TiO2 hollow sphere with a shell size of about 0.5 μm.
[0061] (2) Preparation of gradient thermosensitive poly (N-isopropylacrylamide) hydrogel: 30 mg of ammonium persulfate (concentration: 1 mg / mL) and 300 μL of 4-hydroxybutyl acrylate (concentration: 10 mg / mL) were added to 30 mL of deionized water. The mixture was placed in a reactor at 180 °C for hydrothermal reaction for 240 min. After being taken out from the reactor lining, the hydrogel was dialyzed in 1 L of ultrapure water for 36 h to obtain a gradient thermosensitive poly (N-isopropylacrylamide) hydrogel with a pore size of 30-200 μm.
[0062] (3) Preparation of hollow multi-shell structure drug complexes: The hollow multi-shell structure microspheres were placed in a vacuum environment, and a 50 mg / mL aqueous solution of clonidine was slowly added thereto. The drugs remaining on the surface were then washed several times with deionized water. The above process was repeated 5 times to obtain hollow multi-shell TiO2 loaded with drugs.
[0063] (4) Preparation of hollow multi-shell structure composite gradient hydrogel: 1 g of poly (N-isopropyl acrylamide) hydrogel was heated at 75 °C and excess water was squeezed out. An aqueous solution containing 10 mg of drug-loaded hollow multi-shell TiO2 (the mass ratio of the drug-containing hollow multi-shell structure to poly (N-isopropyl acrylamide) hydrogel was 2:100) and 80 mg / mL of menthol was added to the poly (N-isopropyl acrylamide) hydrogel to allow the hollow multi-shell structure to completely penetrate into the poly (N-isopropyl acrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropyl acrylamide) hydrogel.
[0064] (5) Preparation of hollow multi-shell structure composite gradient hydrogel patch: The hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel is prepared into a hollow multi-shell structure composite gradient hydrogel patch, which includes, from the inside to the outside, a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel layer, a water absorption layer, and a hydroxypropyl cellulose backing transdermal surface layer containing a medical adhesive. Example 3
[0065] A hollow multi-shell structure SiO2 composite gradient temperature-sensitive poly N-isopropylacrylamide hydrogel loaded with propranolol hydrochloride comprises the following steps:
[0066] (1) Preparation of hollow multi-shell SiO2: A 1.5 M sucrose aqueous solution was hydrothermally reacted at 200 °C for 146 min, naturally cooled and filtered, washed with water three times, and placed in a 60 °C oven for 16 h to obtain a carbon sphere template with a diameter of 2.8 μm; the obtained carbon sphere template was dispersed in 30 mL of 3 M Na2O·nSiO2 solution, and the carbon spheres were evenly dispersed by ultrasound. The product was placed in a 30 °C water bath for heating and adsorption for 18 h, centrifuged and washed with deionized water three times, and dried in a 60 °C oven for 18 h to obtain a precursor. The product was placed in a muffle furnace, heated to 500 °C at 2 °C / min, and kept warm for 3 h. After cooling naturally, a three-shell SiO2 hollow sphere with a shell size of about 0.5 μm was obtained.
[0067] (2) Preparation of gradient thermosensitive poly (N-isopropylacrylamide) hydrogel: 3 g of N-isopropylacrylamide aqueous solution (concentration: 100 mg / mL) was added to 30 mL of deionized water, and 90 mg of ammonium persulfate (concentration: 3 mg / mL) and 600 μL of 4-hydroxybutyl acrylate (concentration: 20 mg / mL) were added. The mixture was placed in a reactor at 180 °C for hydrothermal reaction for 240 min. After being taken out from the reactor lining, it was dialyzed in 1 L of ultrapure water for 12 h to obtain a gradient thermosensitive poly (N-isopropylacrylamide) hydrogel with a pore size of 30~200 μm.
[0068] (3) Preparation of hollow multi-shell structure drug complexes: The hollow multi-shell structure microspheres were placed in a vacuum environment, and a 20 mg / mL propranolol hydrochloride aqueous solution was slowly added thereto. The drugs remaining on the surface were then washed several times with deionized water. The above process was repeated 8 times to obtain hollow multi-shell SiO2 loaded with drugs.
[0069] (4) Preparation of hollow multi-shell structure composite gradient hydrogel: 1 g of poly (N-isopropylacrylamide) hydrogel was heated at 80 °C and excess water was squeezed out. Then, a solution of hollow multi-shell SiO2 loaded with drugs (the mass ratio of the hollow multi-shell structure containing drugs to poly (N-isopropylacrylamide) hydrogel was 1:100) and 30 mg / mL of azone was added to the poly (N-isopropylacrylamide) hydrogel to allow the hollow multi-shell structure to completely penetrate into the poly (N-isopropylacrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel.
[0070] (5) Preparation of hollow multi-shell structure composite gradient hydrogel patch: The hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel is prepared into a hollow multi-shell structure composite gradient hydrogel patch, which includes, from the inside to the outside, a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel layer, a water absorption layer, and a polyacrylic acid backing transdermal surface layer containing a medical adhesive. Example 4
[0071] A hollow multi-shell structure Fe2O3 composite gradient temperature-sensitive poly-N-isopropylacrylamide hydrogel loaded with propranolol hydrochloride comprises the following steps:
[0072] (1) Preparation of hollow multi-shell Fe2O3: A 1.5 M sucrose aqueous solution was hydrothermally reacted at 200 °C for 146 min, naturally cooled and filtered, washed with water three times, and placed in a 60 °C oven for 16 h to obtain a carbon sphere template with a diameter of 2.8 μm; the obtained carbon sphere template was dispersed in 30 mL of 3 M Fe(NO3)3 solution, and the carbon spheres were evenly dispersed by ultrasound. The product was placed in a 30 °C water bath for heating and adsorption for 18 h, centrifuged and washed with deionized water three times, and dried in a 60 °C oven for 18 h to obtain a precursor. The product was placed in a muffle furnace, heated to 500 °C at 2 °C / min, and kept warm for 3 h. After cooling naturally, a three-shell Fe2O3 hollow sphere with a size of about 1.5 μm was obtained.
[0073] (2) Preparation of gradient thermosensitive poly (N-isopropylacrylamide) hydrogel: 1.5 g of N-isopropylacrylamide aqueous solution (concentration: 50 mg / mL) was added to 30 mL of deionized water, and 15 mg of ammonium persulfate (concentration: 0.5 mg / mL) and 150 μL of 4-hydroxybutyl acrylate (concentration: 5 mg / mL) were added. The solution was placed in a reactor at 250 °C for hydrothermal reaction for 260 min. After being taken out from the reactor lining, it was dialyzed in 1 L of ultrapure water for 12 h to obtain a gradient thermosensitive poly (N-isopropylacrylamide) hydrogel with a pore size of 30~200 μm.
[0074] (3) Preparation of hollow multi-shell structure drug complexes: The hollow multi-shell structure microspheres were placed in a vacuum environment, and 80 mg / mL propranolol hydrochloride aqueous solution was slowly added thereto. The drugs remaining on the surface were then washed several times with deionized water. The above process was repeated three times to obtain hollow multi-shell Fe2O3 loaded with drugs.
[0075] (4) Preparation of hollow multi-shell structure composite gradient hydrogel: 1 g of poly (N-isopropylacrylamide) hydrogel was heated at 40 °C and excess water was squeezed out. Then, an aqueous solution of drug-loaded hollow multi-shell Fe2O3 (the mass ratio of drug-loaded hollow multi-shell structure to poly (N-isopropylacrylamide) hydrogel was 1:100) and 10 mg / mL azone was added to the poly (N-isopropylacrylamide) hydrogel to allow the hollow multi-shell structure to completely penetrate into the poly (N-isopropylacrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel.
[0076] (5) Preparation of hollow multi-shell structure composite gradient hydrogel patch: The hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel is prepared into a hollow multi-shell structure composite gradient hydrogel patch, which includes, from the inside to the outside, a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel layer, a water absorption layer, and a polyacrylic acid backing transdermal surface layer containing a medical adhesive. Example 5
[0077] A hollow multi-shell structure ZnO composite gradient temperature-sensitive poly (N-isopropylacrylamide) hydrogel loaded with propranolol hydrochloride comprises the following steps:
[0078] (1) Preparation of hollow multi-shell ZnO: A 1.5 M sucrose aqueous solution was hydrothermally reacted at 200 °C for 146 min, naturally cooled and filtered, washed with water three times, and placed in a 60 °C oven for 16 h to obtain a carbon sphere template with a diameter of 2.8 μm; the obtained carbon sphere template was dispersed in 30 mL of a 3 M Zn(NO3)2 solution, and the carbon spheres were evenly dispersed by ultrasound. The product was placed in a 30 °C water bath for heating and adsorption for 18 h, centrifuged and washed with deionized water three times, and dried in a 60 °C oven for 24 h to obtain a precursor. The product was placed in a muffle furnace, heated to 500 °C at 2 °C / min, and kept warm for 3 h. After natural cooling, it was obtained to obtain a three-shell ZnO hollow sphere with a size of about 0.8 μm.
[0079] (2) Preparation of gradient thermosensitive poly (N-isopropylacrylamide) hydrogel: 4.5 g of N-isopropylacrylamide aqueous solution (concentration: 150 mg / mL) was added to 30 mL of deionized water, and 300 μL of ammonium persulfate (concentration: 1 mg / mL) and 4-hydroxybutyl acrylate (concentration: 10 mg / mL) were added. The mixture was placed in a reactor at 150 °C for hydrothermal reaction for 300 min. After being taken out from the reactor lining, it was dialyzed in 1 L of ultrapure water for 24 h to obtain a gradient thermosensitive poly (N-isopropylacrylamide) hydrogel with a pore size of 30-200 μm.
[0080] (3) Preparation of hollow multi-shell structure drug complexes: The hollow multi-shell structure microspheres were placed in a vacuum environment, and a 60 mg / mL propranolol hydrochloride aqueous solution was slowly added thereto. The drugs remaining on the surface were then washed several times with deionized water. The above process was repeated 4 times to obtain hollow multi-shell ZnO loaded with drugs.
[0081] (4) Preparation of hollow multi-shell structure composite gradient hydrogel: 1 g of hydrogel was heated at 90 °C and excess water was squeezed out. An aqueous solution of drug-loaded hollow multi-shell ZnO (the mass ratio of drug-loaded hollow multi-shell structure to poly (N-isopropylacrylamide) hydrogel was 1:100) and 30 mg / mL azone was added to the poly (N-isopropylacrylamide) hydrogel to allow the hollow multi-shell structure to completely penetrate into the poly (N-isopropylacrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel.
[0082] (5) Preparation of hollow multi-shell structure composite gradient hydrogel patch: The hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel is prepared into a hollow multi-shell structure composite gradient hydrogel patch, which includes, from the inside to the outside, a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel layer, a water absorption layer, and a chitosan backing transdermal surface layer containing a medical adhesive. Example 6
[0083] A 2% hollow multi-shell structure TiO2 composite gradient temperature-sensitive poly-N-isopropylacrylamide hydrogel loaded with propranolol hydrochloride comprises the following steps:
[0084] (1) Preparation of hollow multi-shell TiO2: A 1.5 M sucrose aqueous solution was hydrothermally reacted at 200 °C for 146 min, naturally cooled and filtered, washed with water three times, and placed in a 60 °C oven for 16 h to obtain a carbon sphere template with a diameter of 2.8 μm; the obtained carbon sphere template was dispersed in 30 mL of 3 M TiCl4 solution, and the carbon spheres were evenly dispersed by ultrasound. The product was placed in a 30 °C water bath for heating and adsorption for 18 h, centrifuged and washed with deionized water three times, and dried in a 60 °C oven for 18 h to obtain a precursor. The product was placed in a muffle furnace, heated to 500 °C at 2 °C / min, and kept warm for 3 h. After cooling naturally, a three-shell TiO2 hollow sphere with a shell size of about 0.5 μm was obtained.
[0085] (2) Preparation of gradient thermosensitive poly (N-isopropylacrylamide) hydrogel: 30 mg of ammonium persulfate (concentration: 1 mg / mL) and 300 μL of 4-hydroxybutyl acrylate (concentration: 10 mg / mL) were added to 30 mL of deionized water. The mixture was placed in a reactor at 180 °C for hydrothermal reaction for 240 min. After being taken out from the reactor lining, it was dialyzed in 1 L of ultrapure water for 36 h to obtain a gradient thermosensitive poly (N-isopropylacrylamide) hydrogel with a pore size of 30-200 μm.
[0086] (3) Preparation of hollow multi-shell structure drug complexes: The hollow multi-shell structure microspheres were placed in a vacuum environment, and 50 mg / mL propranolol hydrochloride methanol solution was slowly added thereto. The drugs remaining on the surface were then washed several times with ethanol. The above process was repeated 5 times to obtain hollow multi-shell TiO2 loaded with drugs.
[0087] (4) Preparation of hollow multi-shell structure composite gradient hydrogel: 1 g of poly (N-isopropylacrylamide) hydrogel was heated at 75 °C and excess water was squeezed out. 20 mg of hollow multi-shell TiO2 (the mass ratio of the drug-containing hollow multi-shell structure to poly (N-isopropylacrylamide) hydrogel was 2:100) and an aqueous solution of 30 mg / mL of azone were added to the poly (N-isopropylacrylamide) hydrogel to allow the hollow multi-shell structure to completely penetrate into the poly (N-isopropylacrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel.
[0088] (5) Preparation of hollow multi-shell structure composite gradient hydrogel patch: The hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel is prepared into a hollow multi-shell structure composite gradient hydrogel patch, which includes, from the inside to the outside, a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel layer, a water absorption layer, and a polyacrylic acid backing transdermal surface layer containing a medical adhesive. Example 7
[0089] A 3% hollow multi-shell structure TiO2 composite gradient temperature-sensitive poly-N-isopropylacrylamide hydrogel loaded with propranolol hydrochloride comprises the following steps:
[0090] (1) Preparation of hollow multi-shell TiO2: A 1.5 M sucrose aqueous solution was hydrothermally reacted at 200 °C for 146 min, naturally cooled and filtered, washed with water three times, and placed in a 60 °C oven for 16 h to obtain a carbon sphere template with a diameter of 2.8 μm; the obtained carbon sphere template was dispersed in 30 mL of 3 M TiCl4 solution, and the carbon spheres were evenly dispersed by ultrasound. The product was placed in a 30 °C water bath for heating and adsorption for 18 h, centrifuged and washed with deionized water three times, and dried in a 60 °C oven for 18 h to obtain a precursor. The product was placed in a muffle furnace, heated to 500 °C at 2 °C / min, and kept warm for 3 h. After cooling naturally, a three-shell ZnO hollow sphere with a shell size of about 0.5 μm was obtained.
[0091] (2) Preparation of gradient thermosensitive poly (N-isopropylacrylamide) hydrogel: 30 mg of ammonium persulfate (concentration: 1 mg / mL) and 300 μL of 4-hydroxybutyl acrylate (concentration: 10 mg / mL) were added to 30 mL of deionized water. The mixture was placed in a reactor at 180 °C for hydrothermal reaction for 240 min. After being taken out from the reactor lining, it was dialyzed in 1 L of ultrapure water for 36 h to obtain a gradient thermosensitive poly (N-isopropylacrylamide) hydrogel with a pore size of 30-200 μm.
[0092] (3) Preparation of hollow multi-shell structure drug complexes: The hollow multi-shell structure microspheres were placed in a vacuum environment, and 50 mg / mL propranolol hydrochloride methanol solution was slowly added thereto. The drugs remaining on the surface were then washed several times with ethanol. The above process was repeated 5 times to obtain hollow multi-shell TiO2 loaded with drugs.
[0093] (4) Preparation of hollow multi-shell structure composite gradient hydrogel: 1 g of poly (N-isopropylacrylamide) hydrogel was heated at 75 °C and excess water was squeezed out. 30 mg of hollow multi-shell TiO2 (the mass ratio of the drug-containing hollow multi-shell structure to poly (N-isopropylacrylamide) hydrogel was 3:100) and 40 mg / mL of an aqueous solution of azone were added to the poly (N-isopropylacrylamide) hydrogel to allow the hollow multi-shell structure to completely penetrate into the poly (N-isopropylacrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel.
[0094] (5) Preparation of hollow multi-shell structure composite gradient hydrogel patch: The hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel is prepared into a hollow multi-shell structure composite gradient hydrogel patch, which includes, from the inside to the outside, a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel layer, a water absorption layer, and a polyacrylic acid backing transdermal surface layer containing a medical adhesive. Example 8
[0095] A 4% hollow multi-shell structure TiO2 composite gradient temperature-sensitive poly-N-isopropylacrylamide hydrogel loaded with propranolol hydrochloride comprises the following steps:
[0096] (1) Preparation of hollow multi-shell TiO2: A 1.5 M sucrose aqueous solution was hydrothermally reacted at 200 °C for 146 min, naturally cooled and filtered, washed with water three times, and placed in a 60 °C oven for 16 h to obtain a carbon sphere template with a diameter of 2.8 μm; the obtained carbon sphere template was dispersed in 30 mL of 3 M TiCl4 solution, and the carbon spheres were evenly dispersed by ultrasound. The product was placed in a 30 °C water bath for heating and adsorption for 18 h, centrifuged and washed with deionized water three times, and dried in a 60 °C oven for 18 h to obtain a precursor. The product was placed in a muffle furnace, heated to 500 °C at 2 °C / min, and kept warm for 3 h. After cooling naturally, a three-shell ZnO hollow sphere with a shell size of about 0.5 μm was obtained.
[0097] (2) Preparation of gradient thermosensitive poly (N-isopropylacrylamide) hydrogel: 30 mg of ammonium persulfate (concentration: 1 mg / mL) and 300 μL of 4-hydroxybutyl acrylate (concentration: 10 mg / mL) were added to 30 mL of deionized water. The mixture was placed in a reactor at 180 °C for hydrothermal reaction for 240 min. After being taken out from the reactor lining, it was dialyzed in 1 L of ultrapure water for 36 h to obtain a gradient thermosensitive poly (N-isopropylacrylamide) hydrogel with a pore size of 30-200 μm.
[0098] (3) Preparation of hollow multi-shell structure drug complexes: The hollow multi-shell structure microspheres were placed in a vacuum environment, and 50 mg / mL propranolol hydrochloride methanol solution was slowly added thereto. The drugs remaining on the surface were then washed several times with ethanol. The above process was repeated 5 times to obtain hollow multi-shell TiO2 loaded with drugs.
[0099] (4) Preparation of hollow multi-shell structure composite gradient hydrogel: 1 g of poly (N-isopropylacrylamide) hydrogel was heated at 75 °C and excess water was squeezed out. 40 mg of hollow multi-shell TiO2 (the mass ratio of the drug-containing hollow multi-shell structure to poly (N-isopropylacrylamide) hydrogel was 4:100) and an aqueous solution of 60 mg / mL azone were added to the poly (N-isopropylacrylamide) hydrogel to allow the hollow multi-shell structure to completely penetrate into the poly (N-isopropylacrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel.
[0100] (5) Preparation of hollow multi-shell structure composite gradient hydrogel patch: The hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel is prepared into a hollow multi-shell structure composite gradient hydrogel patch, which includes, from the inside to the outside, a hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel layer, a water absorption layer, and a polyacrylic acid backing transdermal surface layer containing a medical adhesive. Comparative Example 1
[0101] 50 mg / mL propranolol hydrochloride solution and 30 mg / mL permeation enhancer azone were added dropwise to a circular poly (N-isopropylacrylamide) hydrogel sheet with a diameter of 2.5 cm to obtain a poly (N-isopropylacrylamide) hydrogel containing a drug solution and a permeation enhancer. Comparative Example 2
[0102] A solution containing 10 mg of the drug is used. Comparative Example 3
[0103] A 50 mg / mL drug solution was added into a circular poly (N-isopropylacrylamide) hydrogel sheet with a diameter of 2.5 cm to obtain a poly (N-isopropylacrylamide) hydrogel containing the drug solution.
[0104] Experimental Example 1 Determination of the compression modulus of hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel
[0105] The hollow multi-shell structure poly-N-isopropylacrylamide hydrogel patch obtained in Examples 1, 6, 7, and 8 was punched into cylindrical specimens with a diameter and height of about 8 mm and 2.5 mm, and was tested on a universal test system equipped with a 10N sensor. The hydrogel sample was compressed in a uniaxial manner between two parallel plates at a compression rate of 1.5 mm / min. The compression modulus was determined based on the slope of the initial linear region of the stress-strain curve.
[0106] The results are as follows Figure 4 As shown, the mechanical properties of the composite gel are significantly enhanced with the increase of the content of hollow multi-shell TiO2.
[0107] Experimental Example 2 Determination of swelling and deswelling properties of hollow multi-shell structure poly (N-isopropylacrylamide) hydrogel
[0108] The hollow multi-shell structure poly N-isopropylacrylamide hydrogel obtained in Example 1 was subjected to swelling and deswelling tests at different temperatures. The steps of the swelling test are as follows: first, the mass of the prepared completely dried hollow multi-shell structure poly N-isopropylacrylamide hydrogel is weighed, recorded as m1, and then the hollow multi-shell structure poly N-isopropylacrylamide hydrogel samples are immersed in PBS solutions of 20-50°C to test their swelling behavior. After keeping at each temperature for 24 hours, the hollow multi-shell structure poly N-isopropylacrylamide hydrogel is taken out, the surface moisture is wiped dry with a moistened filter paper, and it is weighed, and the mass m2 of the hydrogel at this temperature point is recorded to examine the swelling rate and stability of the gel at different temperatures in the PBS solution. The steps of the deswelling test are as follows: first, the hollow multi-shell structure poly N-isopropylacrylamide hydrogel that reaches swelling equilibrium at 20°C is weighed, recorded as W 20 Then, the equilibrium swollen hollow multi-shell structure poly N-isopropyl acrylamide hydrogel was placed in 50°C deionized water to deswell. At regular intervals, the hollow multi-shell structure poly N-isopropyl acrylamide hydrogel was taken out and weighed, which was recorded as W. t After the deswelling was completed, the gel was placed in a 50°C vacuum drying oven and dried for 48 hours. The mass of the dry gel was weighed and recorded as W. d , the water retention rate in the gel after time t is calculated by the formula.
[0109] like Figure 5 As shown, the swelling and deswelling curves indicate that when the temperature varies between 25-30°C, the equilibrium swelling rate will remain at a high level, will drop sharply after the temperature exceeds 30°C, and will remain at a low level after exceeding 40°C; in an environment exceeding the phase transition temperature, the hollow multi-shell structured poly (N-isopropylacrylamide) hydrogel has extremely fast temperature responsiveness, and a large amount of water can be discharged in just 120s.
[0110] Test Example 3 In vitro drug release performance determination
[0111] The hollow multi-shell structure poly N-isopropylacrylamide hydrogel obtained in Example 1 was placed in 5 mL of phosphate buffer solution (PBS) at pH 7.0 to simulate the in vivo environment. The PBS solution containing the hollow multi-shell structure poly N-isopropylacrylamide hydrogel was then carefully transferred to a dialysis bag with a molecular weight cutoff of 14000Da. Subsequently, the dialysis bag containing the sample was placed in a container containing 145 mL of PBS buffer with the same pH value. During the dialysis process, the container was maintained at a constant temperature to better simulate the temperature environment in the human body, and supernatant samples were taken from the external buffer at regular intervals. The absorbance of the supernatant was measured at wavelengths of 230nm and 306nm using UV-visible spectroscopy to study the release behavior of the patch.
[0112] like Figure 6 As shown, the drug release curves showed that propranolol hydrochloride and the permeation enhancer were released in an obvious sequential manner, wherein the permeation enhancer in the poly (N-isopropylacrylamide) hydrogel was released rapidly, while the propranolol hydrochloride in the TiO2 hollow multi-shell structure showed a sustained release.
[0113] Test Example 4 In vitro transdermal performance measurement
[0114] Example 1, Comparative Examples 1, 2, and 3 were applied to rat skin for 36 hours and placed on a Franz diffusion cell, a certain amount of deionized water was added to the receiving cell of the diffusion cell, samples were taken at regular intervals, and the drug content released in the water was measured using a UV-visible spectrophotometer to study the drug release behavior of the patch.
[0115] like Figure 7 As shown, the curve of drug transdermal permeation changing with time indicates that the hollow multi-shell structure composite gradient hydrogel patch improves the skin permeability of the drug within 24 hours of skin application.
[0116] Experimental Example 5 Permeation imaging of hollow multi-shell structures in the skin
[0117] The TiO2-hollow multi-shell composite gradient hydrogel patch labeled with anthocyanin dye Cy7 was applied to the rat skin and placed on a Franz diffusion cell. After 8 hours, the rat skin samples were collected. The samples were processed as follows: (1) frozen and embedded and made into longitudinal sections of the skin, and the fluorescence distribution of the skin section was observed using a fluorescence microscope; (2) the skin was cut into appropriate sizes and fixed with 4% paraformaldehyde buffer for 24 hours, paraffin-embedded and made into paraffin sections for HE staining, and the sections were observed using a microscope.
[0118] like Figure 8 As shown, the deposition of TiO2-hollow multi-shell structures in the stratum corneum of the skin can be seen; Fig. 9 As shown, the red fluorescently labeled hollow multi-shell structures are mainly concentrated in the stratum corneum of the skin, and obvious red fluorescent signals can also be observed in the hair follicles. Combining these observations, we can draw the following conclusions: After the rats were treated with the hollow multi-shell structure composite gradient hydrogel patch, the hollow multi-shell structure was able to accumulate in its stratum corneum.
[0119] Test Example 6 Determination of blood drug concentration in vivo
[0120] The sustained-release patch obtained in Example 1 was applied to the hairless skin of rats for 2 h, 8 h, and 24 h, and blood was taken from the rats at regular intervals to extract the drug. The drug content in the blood was determined by high performance liquid chromatography to study the drug release behavior of the patch.
[0121] in, Fig.10 It is a drug-time curve in blood. It can be seen that the rats using the hollow multi-shell structure composite gradient hydrogel patch, compared with the poly N-isopropylacrylamide hydrogel patch in Comparative Example 1, have a blood drug concentration in the body that can be maintained in the effective drug range for a long time, and as the patch use experiment is extended, the drug absorption amount increases. Therefore, the hollow multi-shell structure composite gradient hydrogel patch can significantly improve the bioavailability of the drug, thereby improving the treatment efficiency.
Claims
1. A method for preparing a hollow multi-shell structure composite gradient hydrogel, characterized in that: The following steps are involved: (1) Preparation of temperature-sensitive hydrogel: N-isopropylacrylamide was added to deionized water, mixed and completely dissolved at room temperature, and then ammonium persulfate and 4-hydroxybutyl acrylate were added and completely dissolved, and a hydrothermal reaction was carried out. After cooling and dialysis, poly N-isopropylacrylamide hydrogel was obtained; The pore size of the obtained poly (N-isopropylacrylamide) hydrogel is 30 to 250 µm, and the pore size gradually decreases from top to bottom. (2) Preparation of hollow multi-shell structure drug complexes: placing the hollow multi-shell structure microspheres in a vacuum environment, adding drug solution thereto, performing vacuum loading, and washing to obtain the drug-loaded hollow multi-shell structure; (3) Preparation of hollow multi-shell structure composite gradient hydrogel: placing poly (N-isopropyl acrylamide) hydrogel in a high temperature environment, causing it to shrink due to heat and discharge excess water, and then dropping a suspension containing a hollow multi-shell structure and a permeation enhancer onto the poly (N-isopropyl acrylamide) hydrogel at room temperature to allow the suspension to penetrate into the pores of the poly (N-isopropyl acrylamide) hydrogel, thereby obtaining a hollow multi-shell structure poly (N-isopropyl acrylamide) hydrogel; The hollow multi-shell structure is one or a combination of oxides TiO2, SiO2, and Fe2O3; The drugs are one or two of propranolol hydrochloride, nitroglycerin, and clonidine.
2. The preparation method according to claim 1, characterized in that: In step (1): The concentration of N-isopropylacrylamide solution is 50-150 mg / mL, the concentration of ammonium persulfate is 0.5-3 g / mL, and the concentration of 4-hydroxybutyl acrylate is 5-20 mg / mL; The hydrothermal reaction temperature is 150-250 ◦ C, hydrothermal reaction time is 200-300min.
3. The preparation method according to claim 1, characterized in that: In step (2): The concentration of the drug solution is 20-80 mg / mL; The size of the prepared hollow multi-shell structures is 0.5-1.5µm; The number of vacuum loading drugs is 3-8 times.
4. The preparation method according to claim 1, characterized in that: In step (2): The cleaning solvent includes one or two of deionized water, methanol, ethanol and chloroform.
5. The preparation method according to claim 1, characterized in that: In step (3): The penetration enhancer is one of water-soluble azone solution, dimethyl sulfoxide, menthol, and sodium lauryl sulfate; The mass ratio of the hollow multi-shell structure to the poly (N-isopropylacrylamide) hydrogel is 1:100-4:
100.
6. The preparation method according to claim 1, characterized in that: The invention also includes the preparation of a composite gradient hydrogel patch with a hollow multi-shell structure: The hollow multi-shell structure poly N-isopropylacrylamide hydrogel is prepared into a hollow multi-shell structure composite gradient hydrogel patch, which includes a hollow multi-shell structure poly N-isopropylacrylamide hydrogel layer, a water absorption layer, and a backing transdermal surface layer from the inside to the outside.
7. The preparation method according to claim 6, characterized in that: The transdermal surface layer of the backing is an adhesive polymer layer, and the polymer layer is polyacrylic acid, chitosan, pectin, hydroxypropyl cellulose, hydroxypropyl methyl cellulose or hydroxyethyl cellulose.
8. Use of the hollow multi-shell structure composite gradient hydrogel obtained according to any one of the preparation methods of claims 1 to 7 in the preparation of transdermal drugs.
9. The hollow multi-shell structure composite gradient hydrogel obtained according to any one of the preparation methods of claims 1 to 5, characterized in that: The hollow multi-shell structure composite gradient hydrogel comprises a hollow multi-shell structure and a poly N-isopropylacrylamide hydrogel with a gradient difference in cross-linking degree. The hollow multi-shell structure is composited in the pores of the poly N-isopropylacrylamide hydrogel through physical or chemical action. The poly N-isopropylacrylamide hydrogel is temperature sensitive. The hollow multi-shell structure composite gradient hydrogel has pores with a gradient change from top to bottom.
